Therapist perceptions of the implementation of a new screening procedure using the ItFits-toolkit in an iCBT routine care clinic: A mixed-methods study using the consolidated framework for implementation research - Tarp, Kristine; Nielsen, Søren Lange; Holmberg, Trine Theresa; Dalsgaard, Caroline Høier; Borkner, Simone; Skaarnes, Helene; Jensen, Esben Kjems; Piera-Jiménez, Jordi; Vis, Christiaan; Mathiasen, Kim (Frontiers in Psychiatry, 2023)
See attached manuscript